Effects of the extremely aggressive atmosphere on structures and equipment of offshore platforms undergoing decommissioning. - Silva Araujo, Leonardo; Chahdan Mounzer, Elie (Revista ALCONPAT, 2025)
The aim of this work was to investigate the influence of an extremely aggressive atmosphere on the metallic structures and equipment of a platform undergoing decommissioning. The methodology included bibliographical research, data collection on accidents caused by corrosion; prior selection of sites; visual inspection; and curation of the data collected. The results showed severe damage to structures, equipment and accessories caused by the intense aggressiveness of the environment. The limitations involved access to information on accidents and incidents related to corrosive processes in this environment. This work is original because it covers the effects of an extremely aggressive atmosphere in the studied environment. The conclusion is that corrosion on platforms in such conditions poses serious risks of structural collapse, as well as potential harm to workers and the environment.